Potential type 2 diabetes mellitus drug HMPA promotes short‐chain fatty acid production by improving carbon catabolite repression effect of gut microbiota. (13th January 2021) - Liu, Huijuan; Qin, Yuan; Li, Kun; Li, Meng; Yang, Jiahuan; Tao, Honglian; Tang, Yuanhao; Yang, Lan; Chen, Shuang; Liu, Yanrong; Yang, Cheng; Gao, Wenqing; et al.
Abstract : Background and Purpose: Gut microbiota plays an important role in type 2 diabetes mellitus (T2DM) progression. From our previous work N ‐(4‐Hydroxyphenethyl)‐3‐mercapto‐2‐methylpropanamide (HMPA) is a potential T2DM drug. We evaluated the effect of HMPA on gut microbiota and studied the molecular mechanism underlying HMPA's regulation of gut microbiota. Experimental Approach: The pseudo germ‐free (PGF) T2DM model and faecal microbiota transplantation method were used to study whether gut microbiota mediates the actions of HMPA. The composition of gut microbiota was detected by using 16S rRNA sequence. Short‐chain fatty acids (SCFAs) content was detected by gas chromatography. The HMPA probe was synthesised for finding and identifying the target protein of HMPA. The effect of HMPA on the utilisation of carbon sources in Bifidobacterium was evaluated. Key Results: HMPA has a slight effect on the PGF T2DM model. The gut microbiota changed by HMPA can also alleviate the symptoms of T2DM. HMPA can regulate gut microbiota structure, increase SCFAs production and reduce nitrate content in the intestinal tissues. The thickness of the mucus on colon tissues increases after HMPA treatment. The target protein of HMPA in gut microbiota is the nitrogen metabolism global transcriptional regulator (GlnR). HMPA promotes the utilisation of less preferred carbon source in the gut microbiota and increases the fermentation product of SCFAs. Conclusion and Implications: HMPA plays a hypoglycaemic role through the gut microbiota. HMPA improves the carbon catabolite repression effect of gut microbiota and increases SCFAs production by targeting GlnR. GlnR may be a target for gut microbiota regulation.